2008
DOI: 10.1007/s11524-008-9301-z
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Geographic Differences in Mammography Screening in St. Louis City: A Multilevel Study

Abstract: To examine racial differences in mammography use and its determinants in the City of St. Louis, MO, USA, we recruited women age 40 or older using randomdigit dialing to (1) examine the difference in mammography use between white women and African American women and (2) identify individual-and census-tract-level risk factors of nonadherence to mammography. During telephone interviews, we inquired about mammography use and several demographic, psychosocial, and health behavior variables. We determined the reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
(51 reference statements)
1
15
0
1
Order By: Relevance
“…Whereas marked racial/ethnic disparities in breast cancer screening were noted historically, 39 our findings are consistent with other studies that report African Americans may actually have higher screening rates than their non-Hispanic white counterparts 40,41 and that differences in screening rates are minimized for members of health maintenance organization (HMO). 42 As seen in other studies, 43 depressive symptomatology has been associated with the underuse of medical screenings, including mammograms, and poor adherence to treatment regimens and a subsequently poorer overall health status.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Whereas marked racial/ethnic disparities in breast cancer screening were noted historically, 39 our findings are consistent with other studies that report African Americans may actually have higher screening rates than their non-Hispanic white counterparts 40,41 and that differences in screening rates are minimized for members of health maintenance organization (HMO). 42 As seen in other studies, 43 depressive symptomatology has been associated with the underuse of medical screenings, including mammograms, and poor adherence to treatment regimens and a subsequently poorer overall health status.…”
Section: Discussionsupporting
confidence: 90%
“…3 Despite the known benefits of annual or biannual screening mammography beginning at age 40 or 50, 4 approximately 25%-50% of American women report not having a mammogram in the past 2 years. 4,5 High variation in average rates of screening mammography adherence can be attributed to the lack of consensus about the efficacy of screening for women aged [40][41][42][43][44][45][46][47][48][49], variation in availability of screening facilities, and other factors that may disproportionately impact those residing in communities with fewer healthcare resources. 6 Elting et al 7 documented that mammography facilities were available in only 49% of Texas counties.…”
mentioning
confidence: 99%
“…They are onerous, as is lack of structural capability in lower income residential areas. There are fewer primary care providers and mammography facilities, less preventive care, and the population often lacks transportation [6,[10][11][12][13][14][15][16][17][18][19][20]. Continuing efforts to reach lower income and African American populations include a community approach that reduces income, insurance, and other structural barriers with free or low-cost mammograms, and mobile units that schedule visits in medically underserved areas (MUAs) [6,8,19].…”
Section: Introductionmentioning
confidence: 99%
“…Since black women are more obese than their white counterparts, one study found out that obesity played some part (30%) in the racial difference at breast cancer diagnosis; however the conclusion of the study was that even after adjustment for obesity, the racial difference in stage of breast cancer at diagnosis still persists. 9 Two studies 10,11 showed that in later years there is a higher incidence of breast cancer in white women than the black women. We observed a statistically significant racial difference among black and white women presenting to EA Conway Medical Center with regards to age at diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Personal-experience barriers to mammography and no physician recommendation also were independently associated with mammography use among white women in this study. 10 Compliance with appointment keeping and alleviating reasons for noncompliance must be considered as factors in breast cancer survival as missed appointments was a determinantof both advanced stage and shorter survival. 12 Important factors affecting breast carcinoma development are reproductive experience, genetics and the environment, effects of endogenous and exogenous hormones, the change in immune status and host vulnerability.Additionally, socioeconomic differences, cultural dynamicsand behavioral characteristics across population subgroups modulate howbiologic disease is expressed among different races and ethnic groups.…”
Section: Resultsmentioning
confidence: 99%